2001
DOI: 10.1302/0301-620x.83b3.10827
|View full text |Cite
|
Sign up to set email alerts
|

Isolated calf lengthening in cerebral palsy

Abstract: We assessed the medium-term outcome of three methods of isolated calf lengthening in cerebral palsy by clinical examination, observational gait analysis and, where appropriate, instrumented gait analysis. The procedures used were percutaneous lengthening of tendo Achillis, open Z-lengthening of tendo Achillis and lengthening of the gastrosoleus aponeurosis (Baker's procedure). We reviewed 195 procedures in 134 children; 45 had hemiplegia, 65 diplegia and 24 quadriplegia. We established the incidence of calcane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
3
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(90 citation statements)
references
References 31 publications
6
80
3
1
Order By: Relevance
“…This finding may be due to excessive retraction being associated with equinus in the hemiplegic population. A study by Borton et al [9] found that males had a significantly increased rate of recurrent equinus following isolated calf lengthening compared to females. It may be that males are more predisposed to equinus in general which in turn means they are more likely to develop pelvic retraction.…”
Section: Discussionmentioning
confidence: 99%
“…This finding may be due to excessive retraction being associated with equinus in the hemiplegic population. A study by Borton et al [9] found that males had a significantly increased rate of recurrent equinus following isolated calf lengthening compared to females. It may be that males are more predisposed to equinus in general which in turn means they are more likely to develop pelvic retraction.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there should be no need to delay until the end of growth, because progression of bone deformities compromises soft tissue procedures. 20,21 Nonoperative treatment aims at functional improvement, postponing surgery to at least the age of 6 years or at avoiding surgery by prevention of a fixed deformity. Additional rationales include improving the patient's ability to wear shoes, the acceptance of orthoses, ease of physical therapy and elimination of disturbances.…”
Section: Nonoperative Treatmentmentioning
confidence: 99%
“…The younger the age of surgical correction, the more likely the recurrence of equinus, due to rapid bone growth that is faster than muscle and tendon growth. 20,28 In diplegia and quadriplegia the timing of surgery is also important. Girls over 7 years old and boys over 8 show much better results, but delayed development of gait or difficulty in predicting the final length and strength of plantarflexors of the foot can be problematic.…”
Section: Botulinum Toxin Type a Botulinum Toxin Type A (Bt-a) Preventsmentioning
confidence: 99%
“…Previous studies have reported recurrent equinus in approximately 10-30% of patients with hemiplegia [11,12] and overcorrection with calcaneus foot in 3-30% of patients with spastic diplegia [10,13,14]. In addition Biedermann et al [15] reported in 2007 a high recurrence rate after calf lengthening with the Ilizarov apparatus for treatment of spastic equinus foot deformity.…”
Section: Introductionmentioning
confidence: 99%